Post Gondwana breakup evolution of the SE Australia rifted margin revisited. (16th December 2019) - McMillan, Malcolm; Gleadow, Andrew; Kohn, Barry; Seiler, Christian
Abstract: Low‐temperature thermochronology (LTT) is commonly used to investigate onshore records of continental rifting and geomorphic evolution of passive continental margins. The SE Australian passive margin, like many others, has an elevated plateau separated from the coastal plain by an erosional escarpment, presumed to originate through Cretaceous rifting prior to Tasman Sea seafloor spreading. Previous LTT studies have focused on reconciling thermal histories with development of the present‐day topography. New apatite LTT data along an escarpment‐to‐coast transect define a classic "boomerang" (mean track length vs. fission‐track age), indicating variable overprinting of late‐Palaeozoic cooling ages by a younger, mid‐Cretaceous cooling event. Regionally, however, the boomerang trend diverges NNW away from the coast and crosses the escarpment, implying the underlying thermal history pre‐dates escarpment formation and is largely independent from post‐breakup landscape evolution. We suggest that Cretaceous cooling might relate to erosion of Permo‐Triassic sedimentary cover from a formerly more extensive Sydney Basin.